2019
DOI: 10.1093/mnras/stz797
|View full text |Cite
|
Sign up to set email alerts
|

A semi-analytical perspective on massive galaxies at z ∼ 0.55

Abstract: The most massive and luminous galaxies in the Universe serve as powerful probes to study the formation of structure, the assembly of mass, and cosmology. However, their detailed formation and evolution is still barely understood. Here we extract a sample of massive mock galaxies from the semi-analytical model of galaxy formation (SAM) Galacticus from the MultiDark-Galaxies, by replicating the CMASS photometric selection from the SDSS-III Baryon Oscillation Spectroscopic Survey (BOSS). The comparison of the Gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 120 publications
(156 reference statements)
0
6
0
Order By: Relevance
“…(iii) The MDPL2-Galacticus Simulation: to test for the effects of sample volume, sample size, and cosmic variance on the strength of correlations of SNIa H 0 estimates with the density field, we will repeat our analyses using the mock data products of MDPL2-Galacticus (Knebe et al 2018), produced by running the Galacticus semi-analytical code (Benson 2012) on the MultiDark Planck 2 (MDPL2) hydrodynamical simulation (Klypin et al 2016). Details are described in Stoppacher et al (2019) and in the above works, but to summarise: the result is a 1 h −3 Gpc 3 box containing 3840 3 Dark Matter particles, whose SDSS ugriz luminosities are traced over cosmic time. In the present work, we make use of the z = 0 redshift snapshot, using corresponding z-band galaxy luminosities to impose a detection-limit on the galaxy sample, in order to construct mock galaxy density fields, used for comparison with the 2MRS K-band observational counterpart.…”
Section: Datamentioning
confidence: 99%
“…(iii) The MDPL2-Galacticus Simulation: to test for the effects of sample volume, sample size, and cosmic variance on the strength of correlations of SNIa H 0 estimates with the density field, we will repeat our analyses using the mock data products of MDPL2-Galacticus (Knebe et al 2018), produced by running the Galacticus semi-analytical code (Benson 2012) on the MultiDark Planck 2 (MDPL2) hydrodynamical simulation (Klypin et al 2016). Details are described in Stoppacher et al (2019) and in the above works, but to summarise: the result is a 1 h −3 Gpc 3 box containing 3840 3 Dark Matter particles, whose SDSS ugriz luminosities are traced over cosmic time. In the present work, we make use of the z = 0 redshift snapshot, using corresponding z-band galaxy luminosities to impose a detection-limit on the galaxy sample, in order to construct mock galaxy density fields, used for comparison with the 2MRS K-band observational counterpart.…”
Section: Datamentioning
confidence: 99%
“…Springel, Di Matteo & Hernquist 2005); conversely, the formation and evolution of the most massive objects known -monstrous passive early-types -is still not completely understood (e.g. Stoppacher et al 2019). Ultimately, they can even present a wide range of morphologies, although being dominated by ellipticals and lenticulars (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that their predictions were in good agreement with different observations from the SDSS (Bernardi et al 2003(Bernardi et al , 2005Wake et al 2006). More recently, Stoppacher et al (2019) used the GALACTICUS SAM (Benson 2012) run on the MultiDark Planck 2 simulation (Klypin et al 2016) to study the galaxy-halo connection and clustering of the BOSS-CMASS DR12 sample (Alam et al 2015), finding good agreement between predictions and observations. Recently, Zhou et al (2020a) presented small-scale (r 20 h −1 Mpc) clustering measurements of DESI-like LRGs selected from the DESI Legacy Imaging Surveys 2 (Dey et al 2019) and fitted their results using the HOD framework.…”
mentioning
confidence: 99%